Difficulties Faced By English Language Students In Phonology Courses - Aisyah Hafizha; Husnul Azizi Fauziah; Yani Lubis (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2023)
Phonology is an important part of sound or sound in language pronunciation, including in English, because inaccurate pronunciation will result in a misunderstanding in communication. The difficulty faced by students lies in the pronunciation of sounds. As for the research method, the researcher used a type/research approach in the form of Library Research. Literature study is used to collect information and data with the help of various materials in the library such as documents, books, magazines, and historical stories.